Assessing the Impact of Aldose Reductase (ALR2) Regulatory Gene Polymorphism in Diabetic Retinopathy Patients - Hadiza Rabe Musa; Amina Rabe Musa; Yahuza Gimba Muhammed; Usman Salisu Batagarawa; Aminu Ibrahim (BioMed Target Journal)
Diabetic retinopathy, a serious complication of diabetes, may be influenced by genetic factors, including the Aldose Reductase (ALR2) gene polymorphism. There is a crucial need to understand how the polymorphism in the ALR2 gene contributes to diabetic retinopathy.  This study aimed to explore and evaluate the impact of ALR2 gene polymorphism on diabetic retinopathy, alongside assessing inflammatory markers and antioxidant status among diabetic patients residing in Kano State, Nigeria. In this study, 40 participants were enrolled; the participants were divided into 4 groups, with three test groups (diabetes mellitus, cataract, and diabetic retinopathy groups) and the control group. The investigation encompassed and incorporated the prevalence of the SNP C(-106)T polymorphism within the ALR2 promoter region, in combination with the assessment of inflammatory markers (C-reactive protein [CRP] and high-sensitivity C-reactive protein [hsCRP]), malondialdehyde (MDA) levels, vitamin A and aldose reductase concentrations. The findings revealed a 6.7% prevalence of the SNP C(-106)T polymorphism. Fasting blood glucose and HbA1c levels were significantly (p<0.05) lower in the control group compared to the diabetic, cataract, and diabetic retinopathy groups. The result also revealed elevated CRP, hsCRP, and MDA levels in the study groups compared to the control group. However, weak negative correlation values were found between vitamin A levels and ALR2 concentrations, indicating a complex relationship that warrants further investigation. Molecular analysis unveiled single nucleotide polymorphisms (SNPs) at nucleotide position -106 within two samples (DR6 and D3). This followed the successful amplification of the specified AR2 gene DNA segment through a Polymerase Chain Reaction (PCR) methodology. Subsequently, DNA sequencing was performed using the ABI Prism BigDyeTM Terminator Cycle Sequencing Ready Reaction Kit on the ABI PrismTM 3730/3730XL DNA Sequencer. In addition, there was no significant (p > 0.05) observed correlation between ALR2 and MDA (r= 0.026) or CRP (r= -0.077).  The study identified a 6.7% prevalence of ALR2 gene polymorphism in diabetic retinopathy patients, alongside elevated inflammatory markers and MDA levels. Moreover, in the present finding, all control group had the C (CC genotype) allele, while the study group had 90% C allele and 10% T allele. The T allele showed no significant association with DR 1.00 (OR 95% CI: 0.127-7.893; p:1.00). However, Additional research with larger sample sizes is warranted to comprehensively investigate the implications of the SNP C(-106)T polymorphism at the ALR2 promoter region.